2017
DOI: 10.1103/physrevc.95.014319
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of α decay for odd- A nuclei within a two-potential approach

Abstract: α decay is usually associated with both ground and low-lying isomeric states of heavy and superheavy nuclei, and the unpaired nucleon plays a key role on α decay. In this work, we systematically studied the α decay half-lives of odd-A nuclei, including both favored and unfavored α decay within the two-potential approach based on the isospin dependent nuclear potential. The α preformation probabilities are estimated by using an analytic formula taking into account the shell structure and proton-neutron correlat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 66 publications
(105 reference statements)
0
27
0
Order By: Relevance
“…26 Recently, we used the two-potential approach (TPA) 27,28 to systematically study the behavior of P α for odd-A and odd-odd nuclei. 29,30 Our results indicated that the P α are smoothly changed with the mass number of parent nuclei for the same kind nuclei. In 2013, Ahmed et al proposed a new quantum-mechanical theory named cluster-formation model (CFM) 31,32 to calculate the α preformation factors of even-even nuclei.…”
Section: Introductionmentioning
confidence: 54%
“…26 Recently, we used the two-potential approach (TPA) 27,28 to systematically study the behavior of P α for odd-A and odd-odd nuclei. 29,30 Our results indicated that the P α are smoothly changed with the mass number of parent nuclei for the same kind nuclei. In 2013, Ahmed et al proposed a new quantum-mechanical theory named cluster-formation model (CFM) 31,32 to calculate the α preformation factors of even-even nuclei.…”
Section: Introductionmentioning
confidence: 54%
“…Firstly, we systematically calculate α preformation factors within the CFM [11][12][13][14][15]. The results are listed in the fifth column of Table I-V. From these tables, we can find that the P α sequence of nuclei from high to low is eveneven nuclei, odd-A nuclei and doubly-odd nuclei, which satisfy the variation tendencies of P α obtained by various models [31][32][33][34][35][36][57][58][59][60]. In order to have a deeper insight into P α , we plot the relationship between P α and NpNn Z0+N0 of even-even nuclei, odd-A nuclei (including favored and unfavored α decay cases) and doubly-odd nuclei (including favored and unfavored α decay cases) around Z = 82, N = 126 closed shells in Fig.…”
Section: Resultsmentioning
confidence: 86%
“…In general, α decay can be approximatively treated as a stationary state problem, on account of the Γ is much smaller than the α decay energy Q α . Hence, we can adopt two-potential approach (TPA), which has been successfully applied to deal with metastable states, to calculate α decay half-life [25][26][27][28][29][30]. In the framework of TPA, the α decay width is calculated as below…”
Section: Theoretical Frameworkmentioning
confidence: 99%